2019
DOI: 10.1111/1759-7714.12982
|View full text |Cite
|
Sign up to set email alerts
|

Annexin 1–nuclear factor‐κB–microRNA‐26a regulatory pathway in the metastasis of non‐small cell lung cancer

Abstract: Background Annexin 1 (ANXA1) expression is associated with the malignant tumor phenotype, making it an attractive therapeutic target. However, little is known about the regulation of ANXA1 in non‐small cell lung cancer (NSCLC). Methods We investigated the biological roles of ANXA1 in tumor growth, migration, and invasion, and explored the possibility of ANXA1 as a potential therapeutic target for the treatment of NSCLC. Results Our findings r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In previous studies, ANXA1 has been reported to both activate and inhibit NF‐κB activity. For example, ANXA1 overexpression in the cytoplasm was shown to constitutively activate NF‐κB through the interaction with the IKK complex in breast cancer cells 32,33 and in NSCLC 34 . However, another research suggested that ANXA1 associated with NF‐kappaB and suppressed its transcriptional activity by preventing NF‐kappaB binding to DNA in colon and pancreatic cancers 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, ANXA1 has been reported to both activate and inhibit NF‐κB activity. For example, ANXA1 overexpression in the cytoplasm was shown to constitutively activate NF‐κB through the interaction with the IKK complex in breast cancer cells 32,33 and in NSCLC 34 . However, another research suggested that ANXA1 associated with NF‐kappaB and suppressed its transcriptional activity by preventing NF‐kappaB binding to DNA in colon and pancreatic cancers 35 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, ANXA1 overexpression in the cytoplasm was shown to constitutively activate NF‐κB through the interaction with the IKK complex in breast cancer cells 32 , 33 and in NSCLC. 34 However, another research suggested that ANXA1 associated with NF‐kappaB and suppressed its transcriptional activity by preventing NF‐kappaB binding to DNA in colon and pancreatic cancers. 35 This echoes its role as either an oncogene‐promoting or oncogene‐suppressing gene in different tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that Annexin A1 may have played a role in the progression of LAC, thus correlating with the occurrence and development of LAC. Some previous studies have suggested that the increase in Annexin A1 is related to the tumorigenesis of lung cancer, including lung squamous cell carcinoma and small cell lung cancer [11][12][13][14]. Our study showed that the expression of Annexin A1 was related to the malignant biological behavior of LAC, including poor differentiation, lymph node metastasis and advanced clinical stage of LAC, suggesting that the expression of Annexin A1 can be considered as a tumor marker to predict the disease progression and prognosis of LAC.…”
Section: Discussionmentioning
confidence: 99%
“…As a proof of principle, it has been demonstrated that Ac 2–26 is able to decrease the proliferation of cervical cancer cells, through the activation of the MAPK family and targeting p53 to arrest the cell cycle ( Cardin et al, 2019 ). It has also been showed that Ac 2–26 could be used to treat non-small cell lung cancer (NSCLC), regulating NFkB pathway ( Guan et al, 2019 ). Remarkably, this ANXA1 mimetic has demonstrated cardioprotective actions against in vivo myocardial infarction, thereby effectively reducing cardiac inflammation, fibrosis and apoptosis ( Qin et al, 2019 ).…”
Section: Annexin A1mentioning
confidence: 99%